The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019 Latin American Robotics Symposium (LARS), 2019 Brazilian Symposium on Robotics (SBR) and 2019 Workshop on Robotics in Educ 2019
DOI: 10.1109/lars-sbr-wre48964.2019.00018
|View full text |Cite
|
Sign up to set email alerts
|

Masking Salient Object Detection, a Mask Region-Based Convolutional Neural Network Analysis for Segmentation of Salient Objects

Abstract: In this paper, we propose a broad comparison between Fully Convolutional Networks (FCNs) and Mask Regionbased Convolutional Neural Networks (Mask-RCNNs) applied in the Salient Object Detection (SOD) context. Studies in the SOD literature usually explore architectures based in FCNs to detect salient regions and objects in visual scenes. However, besides the promising results achieved, FCNs showed issues in some challenging scenarios. Fairly recently studies in the SOD literature proposed the use of a Mask-RCNN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Additionally, our proposed framework ease the addition of other modules such as image processing, classification, object detection, semantic segmentation, and some others novel deep learning methods that explore domain adaptation and data generation that can run on the remote server and make use of Hardware-accelerated Deep Neural Networks running on GPU [30], [31], [32], [33].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our proposed framework ease the addition of other modules such as image processing, classification, object detection, semantic segmentation, and some others novel deep learning methods that explore domain adaptation and data generation that can run on the remote server and make use of Hardware-accelerated Deep Neural Networks running on GPU [30], [31], [32], [33].…”
Section: Discussionmentioning
confidence: 99%
“…It is a pixel-level classification technique with three major tasks: classification, localization, and segmentation. Krinski et al [9] conducted research that with clear images, Mask region-based CNN (R-CNN) outperforms fully convolutional network (FCN). Valada et al [5] demonstrated that ParseNet and AdapNet show high accuracy in detecting objects in images with severe driving conditions.…”
Section: Related Workmentioning
confidence: 99%
“…Valada et al [5] demonstrated that ParseNet and AdapNet show high accuracy in detecting objects in images with severe driving conditions. Many studies with segmentation have improved object detection performance, but the accuracy still stays around 80% [5][6][7][8][9][10]. The accuracy of most segmentation algorithms is higher than Yolo algorithms', but the efficiency is much worse [11][12][13].…”
Section: Related Workmentioning
confidence: 99%
“…In recent decades, the SOD literature presented an impressive growth in the number of novel and promising approaches. Recent works, which are based on Deep Learning techniques, have shown remarkable results in the field [2], [3]. Due to its high precision and generalization abilities, Deep Learningbased methods can find the salient regions of images with higher reliability.…”
Section: Introductionmentioning
confidence: 99%